2016
DOI: 10.1002/jso.24189
|View full text |Cite
|
Sign up to set email alerts
|

Updated long‐term survival for patients with metastatic colorectal cancer treated with liver resection followed by hepatic arterial infusion and systemic chemotherapy

Abstract: Background and Objectives Patients who undergo liver resection for metastatic colorectal cancer (mCRC) have reported 5-year survivals ranging from 25-50%. The current study updated long-term survival for patients with resected liver metastases treated with adjuvant hepatic arterial infusion (HAI) and systemic (SYS) chemotherapy. Methods Updated survival and recurrence free survival for patients treated on four consecutive adjuvant protocols with HAI and SYS from 1991 to 2009. Patients were divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Although our study patients all presented with an extensive burden of disease, the predicted 5‐year OS for patients who were able to convert to complete resection was 63%, which is similar to the rate seen in patients with initially resectable disease, and higher than that demonstrated among patients converted to resection with SYS chemotherapy alone . This may represent an additional survival benefit from improved targeted local disease control with the addition of HAI chemotherapy . These findings strongly support the use of combination HAI and SYS chemotherapy as a therapeutic strategy to improve the rate of conversion to resection and optimize long‐term disease control.…”
Section: Discussionsupporting
confidence: 71%
“…Although our study patients all presented with an extensive burden of disease, the predicted 5‐year OS for patients who were able to convert to complete resection was 63%, which is similar to the rate seen in patients with initially resectable disease, and higher than that demonstrated among patients converted to resection with SYS chemotherapy alone . This may represent an additional survival benefit from improved targeted local disease control with the addition of HAI chemotherapy . These findings strongly support the use of combination HAI and SYS chemotherapy as a therapeutic strategy to improve the rate of conversion to resection and optimize long‐term disease control.…”
Section: Discussionsupporting
confidence: 71%
“…The treatment of metastatic disease localized to the liver has allowed for the successful addition of highly effective regional hepatic therapies, such as hepatic arterial infusion pump (HAIP) therapy, which have contributed to increasing response and survival rates, including disease cure. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Use of HAI in patients with CLM was safe and effective in a randomized controlled trial, demonstrating improved OS in CLM patients who underwent HAI + systemic therapy (68 months) versus systemic therapy alone (55 months). 25,26 More recently, a retrospective series of 2,368 CLM patients undergoing complete metastasectomy with (n = 785) and without (n = 1583) perioperative HAI therapy revealed that patients receiving HAI + systemic chemotherapy had significantly longer OS (67 months) than those treated with systemic therapy alone (44 months). 10 Despite these encouraging results, molecular markers associated with clinical outcomes, response to therapy, or stratification of prognosis have not been systematically examined in CLM patients receiving HAI.…”
Section: Discussionmentioning
confidence: 99%